The ‘dark side’ of the LEAP CCT programme in Ghana: : A critique of the proxy means test (PMT) targeting mechanism - Puorideme, Dennis (Communication & Language at Work, 2020)
Studies of social transfer targeting practices and mechanisms, including the proxy means test (PMT) instrument, have often assumed that the essential purpose of these mechanisms is to ensure fairness, cost-effectiveness and efficiency, yet there is limited consensus on their optimal performance. This article builds on recent studies of social transfer targeting practices in developing countries by providing a better interpretation of the power dynamics involved in ‘translating’ the PMT instrument at the intersection of official, public and cultural discourses. It is a Foucault-based study that combines ethnography and discourse studies to analyse the everyday actions and practices of programme officials and caregivers. This study demonstrates that officials legitimise and translate the PMT instrument, separate individuals from families, and constitute them as objects for governmental intervention to achieve efficiency and cost-effectiveness. The re-categorisation of family members into households ‘outside’ of everyday sociocultural relations and practices is contested and resisted, creating a complex system of power relationships around the PMT.